2014
DOI: 10.1111/joim.12257
|View full text |Cite
|
Sign up to set email alerts
|

Urine soluble urokinase‐type plasminogen activator receptor levels correlate with proteinuria in Puumala hantavirus infection

Abstract: Objectives Urokinase-type plasminogen activator receptor (uPAR) is upregulated during inflammation and known to bind to β3-integrins, receptors used by pathogenic hantaviruses to enter endothelial cells. It has been proposed that soluble uPAR (suPAR) is a circulating factor that causes focal segmental glomerulosclerosis and proteinuria by activating β3-integrin in kidney podocytes. Proteinuria is also a characteristic feature of hantavirus infections. The aim of this study was to evaluate the relation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…6) 3134 . This rationale is supported by the fact that the APOL1 gene encodes a signal peptide sequence that targets newly synthesized protein for secretion, by the fact that exogenously added APOL1 risk-variant proteins, but not the non-risk-variant, affected endocytic machinery within podocytes (formation of autophagosomes)—the mechanism through which APOL1 risk proteins lyse trypanosomes 29 —and lastly, by studies describing suPAR–β 3 integrin-dependent endocytosis of hantaviruses 35,36 . Interestingly, a previous study showed that podocyte-specific expression of APOL1 risk variants in mice resulted in moderate podocyte depletion later in life and occasional preeclampsia 9 .…”
Section: Discussionmentioning
confidence: 99%
“…6) 3134 . This rationale is supported by the fact that the APOL1 gene encodes a signal peptide sequence that targets newly synthesized protein for secretion, by the fact that exogenously added APOL1 risk-variant proteins, but not the non-risk-variant, affected endocytic machinery within podocytes (formation of autophagosomes)—the mechanism through which APOL1 risk proteins lyse trypanosomes 29 —and lastly, by studies describing suPAR–β 3 integrin-dependent endocytosis of hantaviruses 35,36 . Interestingly, a previous study showed that podocyte-specific expression of APOL1 risk variants in mice resulted in moderate podocyte depletion later in life and occasional preeclampsia 9 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, hantavirus infection of renal glomerular (e.g., podocytes) and tubular cells results in disruption of cell-cell contacts that could directly lead to decreased kidney barrier function and subsequent proteinuria ( Krautkramer et al, 2011 ). Also, soluble urokinase-type plasminogen activator receptor (suPAR), elevated in the plasma and urine of HFRS patients, could affect podocyte integrity ( Outinen et al, 2013 , 2014 ).…”
Section: Complement Activationmentioning
confidence: 99%
“…The study cohort consisted of 556 PUUV-infected patients, who had participated in our previous clinical studies [12,17,18,19,24,25,26,27,28,29,30,31,32,33,34,37,38,39,40,41]. The diagnosis of acute PUUV infection was serologically confirmed in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…However, plasma C-reactive protein (CRP) concentration is not associated with the severity of AKI, and it may even be a protective factor for kidney function [25,26,27,28,29,30]. Furthermore, urinary IL-6 and suPAR excretion correlate with proteinuria, which possibly reflects the local production of these molecules in the kidney [31,32]. Nevertheless, the long-term prognosis of acute PUUV infection has been shown to be favorable and is not predicted by the clinical severity of the acute infection [33,34].…”
Section: Introductionmentioning
confidence: 99%